High-transmittance, high-temperature-resistant and high-toughness polyimide material, and preparation method and application thereof
Patent Information
- Application Number
- CN202610752966.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-28
- Publication Date
- 2026-08-28
AI Technical Summary
传统芳香族PI因分子链共轭与电荷转移络合(CTC)作用强,可见光透过率低、颜色深黄、无法满足高透光场景;而通过引入柔性链段增韧时,常伴随耐热性大幅下降;采用有机溶剂聚合则存在污染大、成本高、溶剂残留等问题
[0032] Beneficial technical effects: This invention combines high-transmittance monomers with fluorine or alicyclic structures, with a polymer structure design of rigid main chain and flexible side chain, and a branched crosslinking structure, using green and pollution-free water as the reaction medium to prepare polyimide materials through aqueous phase polymerization. The resulting materials have high visible light transmittance and good heat resistance, as well as good toughness. Due to their good optical, mechanical and heat resistance properties, the prepared materials are suitable for high-end optical applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyimide synthesis technology, specifically to a high-transmittance, high-temperature resistant, and high-toughness polyimide material, its preparation method, and its applications. Background Technology
[0002] High-performance polymers possess excellent mechanical, chemical, and thermal stability, making them the preferred lightweight materials for operating conditions where "soft" polymers fail. Extremely demanding conditions for polymer materials include high temperatures and mechanical strain, such as in electronic devices; or corrosive environments at elevated temperatures, such as in fuel cells. High-performance polymer categories include polybenzimidazoles, polyarylene ethers, aromatic polyamides, and polyimides, all characterized by the presence of aromatic and / or heterocyclic rings in their macromolecular backbone. The latter offer advantages such as glass transition temperatures (Tg) greater than 200°C and high chemical resistance. The disadvantage is that the formation and processing of these polymers require harsh conditions. For example, polyimides are typically obtained in toxic solvents such as cresol, xylene, and chlorobenzene at reaction temperatures of several hundred degrees Celsius.
[0003] However, polyimide (PI) is widely used in aerospace, microelectronics, and semiconductor packaging due to its outstanding thermal stability, mechanical properties, and electrical insulation. Traditional aromatic PI has low visible light transmittance and a deep yellow color due to strong molecular chain conjugation and charge transfer complexation (CTC), making it unsuitable for high-transmittance applications. Introducing flexible segments for toughening often results in a significant decrease in heat resistance. Polymerization using organic solvents leads to problems such as high pollution, high cost, and solvent residue.
[0004] Currently, high-transmittance polyimides are typically synthesized using fluorinated monomers or alicyclic monomers, but these methods generally suffer from prominent problems such as low toughness, difficulty in simultaneously achieving both heat resistance and light transmittance, susceptibility to cracking during molding and processing, and immature water-based polymerization processes. Existing technologies struggle to simultaneously achieve high visible light transmittance, heat resistance, and high toughness in a single material, and most rely on organic solvent systems, failing to meet the industrial demands for green aqueous phase polymerization, stable and controllable processes, and scalable production. Therefore, developing a polyimide material that integrates green aqueous phase polymerization, high transmittance, high temperature resistance, and high toughness has become a pressing technical challenge for the high-end optics and equipment field. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a high-transmittance, high-temperature-resistant, and high-toughness polyimide material, its preparation method, and its applications. This invention utilizes a blend of high-transmittance monomers with fluorine-containing or alicyclic structures, combined with a polymer structure design featuring a rigid main chain and flexible side chains, and a three-dimensional branched crosslinking structure. The resulting polyimide material, obtained through aqueous phase polymerization, simultaneously exhibits high visible light transmittance, heat resistance, and high toughness. The synthesis method is green and pollution-free, making it suitable for high-end optical applications.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0007] A high-transmittance, high-temperature resistant, and high-toughness polyimide material is prepared by aqueous phase polymerization comprising the following molar percentages of monomers:
[0008] The composition of the first rigid monomer is 35%-50%, the second rigid monomer is 25%-35%, the flexible monomer is 12%-20%, and the crosslinking monomer is 0.5%-5%.
[0009] The first rigid monomer is prepared by mixing hexafluorodianhydride (6FDA, refractive index 1.556) and cyclobutanetetracarboxylic dianhydride (refractive index 1.599) in a molar ratio of 1:1.2-1.5;
[0010] The second rigid monomer is prepared by mixing 2,2'-bis(trifluoromethyl)biphenyldiamine (refractive index 1.524) with a diaminodiphenyl ether compound with a refractive index of 1.6 or higher in a molar ratio of 0.8-1.5:1;
[0011] The flexible monomer is prepared by mixing 2,2'-bis[4-(4-aminophenoxy)phenyl]propane (refractive index 1.641) and 1,4-bis(2-trifluoromethyl4-aminophenoxy)benzene (CAS No. 94525-05-0, refractive index 1.559) in a molar ratio of 1-1.5:1.
[0012] The crosslinking monomer is a three-dimensional compound containing at least three amino groups.
[0013] Furthermore, the diaminodiphenyl ether compound is selected from one or more of 4,4'-diaminodiphenyl ether (refractive index 1.666), 3,4'-diaminodiphenyl ether (refractive index 1.666), 2,2'-diaminoethylene glycol diphenyl ether (refractive index 1.631), 1,3-bis(3-aminophenoxy)benzene (refractive index 1.668), 4,4'-diaminodiphenyl sulfide (refractive index 1.707), 4,4'-diaminodiphenyl disulfide (refractive index 1.741), and 2,2'-diaminodiphenyl sulfide (refractive index 1.707).
[0014] Furthermore, the three-component compounds containing at least three amino groups are selected from one or more of 1,3,5-triaminobenzene, 4,4',4''-triaminotriphenylmethane, 2,3,6,7,10,11-hexaaminotriphenyl, benzo[a]phenanthrene-1,5,9-triamine, tris(3,5-bis(4'-aminophenyl)benzene)trimethylbenzene, and triamterene. The three-component structure increases the degree of branching, and these compounds all have high refractive indices.
[0015] Furthermore, the physicochemical properties of the polyimide material satisfy the following conditions ①-④:
[0016] ① 550 nm visible light transmittance ≥ 88%;
[0017] ② Yellowness index YI < 3.0;
[0018] ③ Elongation at break ≥ 10%;
[0019] ④ 5wt% thermal weight loss temperature ≥ 550℃.
[0020] The preparation method of the above-mentioned high-transmittance, high-temperature resistant and high-toughness polyimide material includes the following steps:
[0021] S1. Preparation of polyamic acid suspension by aqueous suspension polymerization: using distilled water as solvent, under nitrogen protection and continuous stirring, add the second rigid monomer and the flexible monomer at a temperature below 60°C. After complete dissolution, add the first rigid monomer in batches, control the reaction temperature to not exceed 65°C, and keep the reaction at the temperature for 4-6 hours to obtain polyamic acid suspension.
[0022] S2, Aqueous phase in-situ imidization: Adjust the pH of the system to 8-9, raise the temperature to 120-130℃ under nitrogen protection, keep the reaction at this temperature for 3-4 hours, and obtain crude PI powder after filtration, washing and drying.
[0023] S3. Post-processing: Under nitrogen protection, the coarse PI powder is heat-treated, cooled, crushed, and sieved to obtain a high-transmittance, high-temperature resistant, and high-toughness polyimide material.
[0024] Furthermore, the concentration of total monomers in water in S1 is 0.5-1.5 mol / L; the nitrogen flow rate in S1 is 30-50 mL / min;
[0025] In S1, the first rigid monomer is added in at least 3 batches, with an interval of at least 10 minutes between each batch.
[0026] Furthermore, in S2, the pH value is adjusted using ammonia water with a mass fraction of 25%-28%; the nitrogen flow rate in S2 is in the range of 50-60 mL / min; and the nitrogen flow rate in S3 is 60-80 mL / min.
[0027] Furthermore, the heat treatment is a gradient heating process, the specific process of which is as follows:
[0028] First, raise the temperature to 80-120℃ at a rate greater than 5℃ / min and hold at this temperature for 1-2 hours;
[0029] Then raise the temperature to 180-250℃ at a rate of 1-5℃ / min and hold at this temperature for 1-2 hours;
[0030] Finally, raise the temperature to 300-320℃ at a rate of less than 1℃ / min and hold at this temperature for 2-3 hours.
[0031] The final aspect of this invention provides the application of the above-mentioned high-transmittance, high-temperature resistant and high-toughness polyimide material in optoelectronic materials and devices.
[0032] Beneficial technical effects: This invention combines high-transmittance monomers with fluorine or alicyclic structures, with a polymer structure design of rigid main chain and flexible side chain, and a branched crosslinking structure, using green and pollution-free water as the reaction medium to prepare polyimide materials through aqueous phase polymerization. The resulting materials have high visible light transmittance and good heat resistance, as well as good toughness. Due to their good optical, mechanical and heat resistance properties, the prepared materials are suitable for high-end optical applications. Detailed Implementation
[0033] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0034] Unless otherwise specifically stated, the numerical values set forth in these embodiments do not limit the scope of the invention. Techniques and methods known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques and methods should be considered part of the specification. In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that values expressed, for example, as "within the range of ab" or "between the range of ab," do not include the endpoint values a and b; values expressed as "for ab," "is ab," or "ab" include the endpoint values a and b.
[0035] Furthermore, it should be noted that the use of terms such as "first" and "second" to define the individual entities is merely for the purpose of distinguishing each entity. Unless otherwise stated, the above terms have no special meaning and therefore should not be construed as limiting the scope of protection of this invention.
[0036] Experimental methods not specified in the following examples are generally performed according to national standards; if there is no corresponding national standard, they are performed according to general standard requirements or general methods.
[0037] Example 1
[0038] A method for preparing a polyimide material with high light transmittance, high temperature resistance, and high toughness includes the following steps:
[0039] S1. Preparation of polyamic acid suspension by aqueous phase suspension polymerization:
[0040] Add 200 mL of distilled water to the reaction vessel, purge with nitrogen gas at a flow rate of 40 mL / min, stir at 300 rpm, and heat to 55 °C. Then, add 9.15 g (320.23 g / mol, 0.02857 mol) of 2,2'-bis(trifluoromethyl)biphenyl diamine, 4.31 g (200.24 g / mol, 0.02152 mol) of 4,4'-diaminodiphenyl ether, 4.92 g (410.51 g / mol, 0.01199 mol) of 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 5.13 g (428.33 g / mol, 0.01198 mol) of 1,4-bis(2-trifluoromethyl4-aminophenoxy)benzene, and 0.45 g (123.16 g / mol, 0.003654 mol) of 1,3,5-triaminobenzene, and stir until completely dissolved.
[0041] 12.83 g of hexafluorodianhydride (6FDA, 444.24 g / mol, 0.02888 mol) and 7.81 g of cyclobutanetetracarboxylic dianhydride (196.11 g / mol, 0.03982 mol) were mixed evenly and added to the above reaction system in 5 batches with an interval of 15 minutes between each batch. The reaction temperature was controlled at 60℃ and kept at this temperature for 5 hours to obtain a polyamic acid suspension.
[0042] S2, in-situ imidization in aqueous phase:
[0043] Adjust the nitrogen flow rate to 50 mL / min, add 25 wt% ammonia to the polyamic acid suspension of S1 to adjust the pH of the system to 8.5, raise the temperature to 125℃ at 2.5℃ / min, and maintain the reaction at this temperature for 3.5 hours. After cooling, centrifuge and filter, wash four times with distilled water, and vacuum dry at 105℃ for 10 hours to obtain crude polyimide powder.
[0044] S3. Post-treatment: The crude polyimide powder is placed in a nitrogen atmosphere for gradient heating treatment. The specific process is as follows: the temperature is increased to 100℃ at a rate of 15℃ / min and held at this temperature for 1.5 hours.
[0045] Then raise the temperature to 200℃ at a rate of 2℃ / min and hold at this temperature for 2 hours;
[0046] Finally, the temperature is increased to 310℃ at a rate of 0.5℃ / min and held at this temperature for 2.5 hours.
[0047] The material is then cooled, pulverized, and passed through a 150-mesh sieve to obtain a high-transmittance, high-temperature resistant, and high-toughness polyimide powder.
[0048] Example 2
[0049] A method for preparing a polyimide material with high light transmittance, high temperature resistance, and high toughness includes the following steps:
[0050] S1. Preparation of polyamic acid suspension by aqueous phase suspension polymerization:
[0051] Add 200 mL of distilled water to the reaction vessel, purge with nitrogen gas at a flow rate of 30 mL / min, stir at 250 rpm, and heat to 50 °C. Then, add 7.39 g of 2,2'-bis(trifluoromethyl)biphenyl diamine (320.23 g / mol, 0.02308 mol), 3.74 g of 4,4'-diaminodiphenyl ether (200.24 g / mol, 0.01868 mol), 4.92 g of 2,2'-bis[4-(4-aminophenoxy)phenyl]propane (410.51 g / mol, 0.01199 mol), 5.13 g of 1,4-bis(2-trifluoromethyl4-aminophenoxy)benzene (428.33 g / mol, 0.01198 mol), and 0.45 g of 1,3,5-triaminobenzene (123.16 g / mol, 0.003654 mol), and stir until completely dissolved.
[0052] 13.82 g of hexafluorodianhydride (6FDA, 444.24 g / mol, 0.03111 mol) and 8.42 g of cyclobutanetetracarboxylic dianhydride (196.11 g / mol, 0.04294 mol) were mixed evenly and added to the above reaction system in 5 batches with an interval of 20 minutes between each batch. The reaction temperature was controlled at 55℃ and kept at this temperature for 4 hours to obtain a polyamic acid suspension.
[0053] S2, in-situ imidization in aqueous phase:
[0054] Adjust the nitrogen flow rate to 50 mL / min, add 25 wt% ammonia to the polyamic acid suspension of S1 to adjust the pH of the system to 8.0, raise the temperature to 120℃ at 2℃ / min and maintain the reaction at this temperature for 4 hours. After cooling, centrifuge and filter, wash three times with distilled water, and vacuum dry at 120℃ for 12 hours to obtain crude polyimide powder.
[0055] S3. Post-treatment: The crude polyimide powder is placed in a nitrogen atmosphere for gradient heating treatment. The specific process is as follows: the temperature is increased to 100℃ at a rate of 6℃ / min and held at this temperature for 1.5 hours.
[0056] Then raise the temperature to 200℃ at a rate of 2℃ / min and hold at this temperature for 2 hours;
[0057] Finally, the temperature is increased to 300℃ at a rate of 0.5℃ / min and held at this temperature for 2.5 hours.
[0058] The material is then cooled, pulverized, and sieved through a 100-mesh sieve to obtain a high-transmittance, high-temperature resistant, and high-toughness polyimide powder.
[0059] Example 3
[0060] A method for preparing a polyimide material with high light transmittance, high temperature resistance, and high toughness includes the following steps:
[0061] S1. Preparation of polyamic acid suspension by aqueous phase suspension polymerization:
[0062] Add 200 mL of distilled water to the reaction vessel, purge with nitrogen gas at a flow rate of 50 mL / min, stir at 350 rpm, and heat to 60 °C. Then, add 10.22 g (320.23 g / mol, 0.03191 mol) of 2,2'-bis(trifluoromethyl)biphenyl diamine, 4.81 g (200.24 g / mol, 0.02402 mol) of 4,4'-diaminodiphenyl ether, 4.92 g (410.51 g / mol, 0.01199 mol) of 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 5.13 g (428.33 g / mol, 0.01198 mol) of 1,4-bis(2-trifluoromethyl4-aminophenoxy)benzene, and 0.56 g (123.16 g / mol, 0.004547 mol) of 1,3,5-triaminobenzene, and stir until completely dissolved.
[0063] 11.75 g of hexafluorodianhydride (6FDA, 444.24 g / mol, 0.02645 mol) and 7.16 g of cyclobutanetetracarboxylic dianhydride (196.11 g / mol, 0.03651 mol) were mixed evenly and added to the above reaction system in 5 batches with an interval of 15 minutes between each batch. The reaction temperature was controlled at 65℃ and kept at this temperature for 6 hours to obtain a polyamic acid suspension.
[0064] S2, in-situ imidization in aqueous phase:
[0065] Adjust the nitrogen flow rate to 60 mL / min, add 28 wt% ammonia to the polyamic acid suspension of S1 to adjust the pH of the system to 9.0, raise the temperature to 130℃ at 3℃ / min and maintain the reaction at this temperature for 3 hours. After cooling, centrifuge and filter, wash 5 times with distilled water, and dry under vacuum at 110℃ for 8 hours to obtain crude polyimide powder.
[0066] S3. Post-treatment: The crude polyimide powder is placed in a nitrogen atmosphere for gradient heating treatment. The specific process is as follows: the temperature is increased to 100℃ at a rate of 6℃ / min and held at this temperature for 1 hour.
[0067] Then raise the temperature to 200℃ at a rate of 2℃ / min and hold at this temperature for 1.5 hours;
[0068] Finally, the temperature is increased to 320℃ at a rate of 0.5℃ / min and held at this temperature for 2 hours.
[0069] The material is then cooled, pulverized, and passed through a 200-mesh sieve to obtain a high-transmittance, high-temperature resistant, and high-toughness polyimide powder.
[0070] Example 4
[0071] A method for preparing a polyimide material with high light transmittance, high temperature resistance, and high toughness includes the following steps:
[0072] S1. Preparation of polyamic acid suspension by aqueous phase suspension polymerization:
[0073] Add 200 mL of distilled water to the reaction vessel, purge with nitrogen gas at a flow rate of 45 mL / min, stir at 320 rpm, and heat to 60 °C. Then, add 9.70 g (320.23 g / mol, 0.03029 mol) of 2,2'-bis(trifluoromethyl)biphenyl diamine, 4.10 g (200.24 g / mol, 0.02048 mol) of 4,4'-diaminodiphenyl ether, 4.88 g (410.51 g / mol, 0.01188 mol) of 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 5.06 g (428.33 g / mol, 0.01182 mol) of 1,4-bis(2-trifluoromethyl4-aminophenoxy)benzene, and 0.42 g (123.16 g / mol, 0.003410 mol) of 1,3,5-triaminobenzene, and stir until completely dissolved.
[0074] 14.20 g of hexafluorodianhydride (6FDA, 444.24 g / mol, 0.03196 mol) and 7.75 g of cyclobutanetetracarboxylic dianhydride (196.11 g / mol, 0.03952 mol) were mixed evenly and added to the above reaction system in 4 batches with an interval of 18 minutes between each batch. The reaction temperature was controlled at 62℃ and kept at this temperature for 5.5 hours to obtain a polyamic acid suspension.
[0075] S2, in-situ imidization in aqueous phase:
[0076] Adjust the nitrogen flow rate to 50 mL / min, add 25 wt% ammonia to the polyamic acid suspension of S1 to adjust the pH of the system to 8.7, raise the temperature to 128℃ at 3℃ / min and maintain the reaction at this temperature for 3.5 hours. After cooling, centrifuge and filter, wash three times with distilled water, and vacuum dry at 120℃ for 12 hours to obtain crude polyimide powder.
[0077] S3. Post-treatment: The crude polyimide powder is placed in a nitrogen atmosphere for gradient heating treatment. The specific process is as follows: the temperature is increased to 110℃ at a rate of 6℃ / min and held at this temperature for 1.5 hours.
[0078] Then raise the temperature to 220℃ at a rate of 2℃ / min and hold at this temperature for 1.8 hours;
[0079] Finally, the temperature was increased to 320℃ at a rate of 0.8℃ / min and held at this temperature for 2.5 hours.
[0080] The material is then cooled, pulverized, and passed through a 150-mesh sieve to obtain a high-transmittance, high-temperature resistant, and high-toughness polyimide powder.
[0081] Example 5
[0082] A method for preparing a polyimide material with high light transmittance, high temperature resistance, and high toughness includes the following steps:
[0083] S1. Preparation of polyamic acid suspension by aqueous phase suspension polymerization:
[0084] Add 200 mL of distilled water to the reaction vessel, purge with nitrogen gas at a flow rate of 40 mL / min, stir at 300 rpm, and heat to 55 °C. Then, add 7.15 g (320.23 g / mol, 0.02233 mol) of 2,2'-bis(trifluoromethyl)biphenyl diamine, 5.54 g (216.30 g / mol, 0.02561 mol) of 4,4'-diaminodiphenyl sulfide, 6.50 g (410.51 g / mol, 0.01583 mol) of 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 6.80 g (428.33 g / mol, 0.01588 mol) of 1,4-bis(2-trifluoromethyl4-aminophenoxy)benzene, and 0.42 g (123.16 g / mol, 0.003410 mol) of 1,3,5-triaminobenzene, and stir until completely dissolved.
[0085] 12.00 g of hexafluorodianhydride (6FDA, 444.24 g / mol, 0.02701 mol) and 7.35 g of cyclobutanetetracarboxylic dianhydride (196.11 g / mol, 0.03748 mol) were mixed evenly and added to the above reaction system in 5 batches with an interval of 15 minutes between each batch. The reaction temperature was controlled at 60℃ and kept at this temperature for 5 hours to obtain a polyamic acid suspension.
[0086] S2, in-situ imidization in aqueous phase:
[0087] Adjust the nitrogen flow rate to 50 mL / min, add 25 wt% ammonia to the polyamic acid suspension of S1 to adjust the pH of the system to 8.5, raise the temperature to 125℃ at 2℃ / min and maintain the reaction at this temperature for 3.5 hours. After cooling, centrifuge and filter, wash three times with distilled water, and dry under vacuum at 100℃ for 12 hours to obtain crude polyimide powder.
[0088] S3. Post-treatment: The crude polyimide powder is placed in a nitrogen atmosphere for gradient heating treatment. The specific process is as follows: the temperature is increased to 100℃ at a rate of 6℃ / min and held at this temperature for 1.5 hours.
[0089] Then raise the temperature to 200℃ at a rate of 2℃ / min and hold at this temperature for 1.8 hours;
[0090] Finally, the temperature was increased to 310℃ at a rate of 0.5℃ / min and held at this temperature for 2.2 hours.
[0091] The material is then cooled, pulverized, and passed through a 150-mesh sieve to obtain a high-transmittance, high-temperature resistant, and high-toughness polyimide powder.
[0092] Example 6
[0093] A method for preparing a polyimide material with high light transmittance, high temperature resistance, and high toughness includes the following steps:
[0094] S1. Preparation of polyamic acid suspension by aqueous phase suspension polymerization:
[0095] Add 200 mL of distilled water to the reaction vessel, purge with nitrogen gas at a flow rate of 50 mL / min, stir at 350 rpm, and heat to 60 °C. Then, add 8.24 g (320.23 g / mol, 0.02573 mol) of 2,2'-bis(trifluoromethyl)biphenyl diamine, 7.06 g (248.37 g / mol, 0.02842 mol) of 4,4'-diaminodiphenyl disulfide, 5.45 g (410.51 g / mol, 0.01328 mol) of 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 5.70 g (428.33 g / mol, 0.01331 mol) of 1,4-bis(2-trifluoromethyl4-aminophenoxy)benzene, and 0.42 g (123.16 g / mol, 0.003410 mol) of 1,3,5-triaminobenzene, and stir until completely dissolved.
[0096] 13.35 g of hexafluorodianhydride (6FDA, 444.24 g / mol, 0.03005 mol) and 7.73 g of cyclobutanetetracarboxylic dianhydride (196.11 g / mol, 0.03944 mol) were mixed evenly and added to the above reaction system in 5 batches with an interval of 15 minutes between each batch. The reaction temperature was controlled at 65℃ and kept at this temperature for 6 hours to obtain a polyamic acid suspension.
[0097] S2, in-situ imidization in aqueous phase:
[0098] Adjust the nitrogen flow rate to 60 mL / min, add 28 wt% ammonia to the polyamic acid suspension of S1 to adjust the pH of the system to 9.0, raise the temperature to 130℃ at 2℃ / min and maintain the reaction at this temperature for 3 hours. After cooling, centrifuge and filter, wash three times with distilled water, and vacuum dry at 120℃ for 12 hours to obtain crude polyimide powder.
[0099] S3. Post-treatment: The crude polyimide powder is placed in a nitrogen atmosphere for gradient heating treatment. The specific process is as follows: the temperature is increased to 100℃ at a rate of 6℃ / min and held at this temperature for 1 hour.
[0100] Then raise the temperature to 200℃ at a rate of 2℃ / min and hold at this temperature for 1.5 hours;
[0101] Finally, the temperature is increased to 315℃ at a rate of 0.5℃ / min and held at this temperature for 2 hours.
[0102] The material is then cooled, pulverized, and passed through a 150-mesh sieve to obtain a high-transmittance, high-temperature resistant, and high-toughness polyimide powder.
[0103] Comparative Example 1
[0104] The polyimide preparation process in this case is the same as in Example 1, except that the flexible monomers 2,2'-bis[4-(4-aminophenoxy)phenyl]propane and 1,4-bis(2-trifluoromethyl4-aminophenoxy)benzene are not added, and the crosslinking monomer is not added.
[0105] Comparative Example 2
[0106] The polyimide preparation process in this case is the same as in Example 1, except that no crosslinking monomer is added.
[0107] Comparative Example 3
[0108] The polyimide preparation process in this case is the same as in Example 1. The difference is that the traditional aromatic monomers 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-diaminodiphenyl ether (ODA) are prepared in a molar ratio of 1:1, and the total molar amount of monomers is the same as in Example 1.
[0109] Test case
[0110] The above material was molded into a circular plate with a thickness of 4 mm and a diameter of 10 cm using a molding machine. After processing, the material was made into a sample to measure its mechanical and optical properties, as shown in Table 1 below.
[0111] Table 1 Properties of polyimide materials in the examples and comparative examples
[0112]
[0113] As shown in Table 1, the light transmittance of the polyimide material prepared in the embodiments of the present invention is at least 88.5%. In Examples 5 and 6, due to the adjustment of the internal ratio of the two substances in the second rigid monomer and the use of high-transmittance diaminodiphenyl sulfide compounds with higher refractive index, the light transmittance reached over 90.5%. Comparative Example 1, due to the absence of a flexible monomer, showed a significant decrease in light transmittance and a significant increase in yellowing index, while also showing a significant decrease in mechanical properties. Comparative Example 2, due to the absence of a three-dimensional crosslinking monomer, showed a decrease in light transmittance to below 83%, a significant decrease in mechanical properties, and a slight decrease in heat resistance. Comparative Example 3, using a traditional aromatic monomer, had poor light transmittance and yellowing index, and its toughness was also unsatisfactory. This was mainly because the traditional aromatic diamine and aromatic dianhydride formed an excited-state charge-transfer complex (CTC) on the main chain due to π-π interactions, resulting in a darker color of the material and severely affecting the light transmittance and yellowing index. Therefore, this invention addresses the adverse effects of CTC on optical performance caused by traditional monomers. By introducing monomers containing strongly negatively charged groups (fluorine atoms) or alicyclic structures into the molecular chain, and combining them with three-dimensional crosslinking monomers, the π-π interactions are weakened and the coplanar stacking of molecular chains is hindered, thereby effectively suppressing the CTC effect and greatly increasing the optical performance of polyimide.
[0114] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A polyimide material with high light transmittance, high temperature resistance, and high toughness, characterized in that, Monomers comprising the following molar percentages were prepared by aqueous phase polymerization: The composition of the first rigid monomer is 35%-50%, the second rigid monomer is 25%-35%, the flexible monomer is 12%-20%, and the crosslinking monomer is 0.5%-5%. The first rigid monomer is prepared by mixing hexafluorodianhydride and cyclobutanetetracarboxylic dianhydride in a molar ratio of 1:1.2-1.5; The second rigid monomer is prepared by mixing 2,2'-bis(trifluoromethyl)biphenyldiamine with a diaminodiphenyl ether compound with a refractive index of 1.6 or higher in a molar ratio of 0.8-1.5:1; The flexible monomer is prepared by mixing 2,2'-bis[4-(4-aminophenoxy)phenyl]propane and 1,4-bis(2-trifluoromethyl4-aminophenoxy)phenyl in a molar ratio of 1-1.5:1; The crosslinking monomer is a three-dimensional compound containing at least three amino groups.
2. The high-transmittance, high-temperature resistant, and high-toughness polyimide material according to claim 1, characterized in that, The diaminodiphenyl ether compounds are selected from one or more of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 2,2'-diaminoethylene glycol diphenyl ether, 1,3-bis(3-aminophenoxy)benzene, 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl disulfide, and 2,2'-diaminodiphenyl sulfide.
3. The high-transmittance, high-temperature resistant, and high-toughness polyimide material according to claim 1, characterized in that, The compound containing at least three amino groups is selected from one or more of 1,3,5-triaminobenzene, 4,4',4''-triaminotriphenylmethane, 2,3,6,7,10,11-hexaaminotriphenyl, benzophenanthrene-1,5,9-triamine, tris(3,5-bis(4'-aminophenyl)benzene)trimethylbenzene, and triamterene.
4. A high-transmittance, high-temperature resistant, and high-toughness polyimide material according to any one of claims 1-3, characterized in that, The physicochemical properties of the polyimide material satisfy the following conditions ①-④: ① 550 nm visible light transmittance ≥ 88%; ② Yellowness index YI < 3.0; ③ Elongation at break ≥ 10%; ④ 5wt% thermal weight loss temperature ≥ 550℃.
5. A method for preparing a polyimide material with high light transmittance, high temperature resistance, and high toughness, characterized in that, The preparation of the polyimide material according to any one of claims 1-4 comprises the following steps: S1. Preparation of polyamic acid suspension by aqueous suspension polymerization: using distilled water as solvent, under nitrogen protection and continuous stirring, add the second rigid monomer and the flexible monomer at a temperature below 60°C. After complete dissolution, add the first rigid monomer in batches, control the reaction temperature to not exceed 65°C, and keep the reaction at the temperature for 4-6 hours to obtain polyamic acid suspension. S2, Aqueous phase in-situ imidization: Adjust the pH of the system to 8-9, raise the temperature to 120-130℃ under nitrogen protection, keep the reaction at this temperature for 3-4 hours, and obtain crude PI powder after filtration, washing and drying. S3. Post-processing: Under nitrogen protection, the coarse PI powder is heat-treated, cooled, crushed, and sieved to obtain a high-transmittance, high-temperature resistant, and high-toughness polyimide material.
6. The method for preparing a high-transmittance, high-temperature resistant, and high-toughness polyimide material according to claim 5, characterized in that, The total monomer concentration in water in S1 is 0.5-1.5 mol / L; the nitrogen flow rate in S1 is 30-50 mL / min; In S1, the first rigid monomer is added in at least 3 batches, with an interval of at least 10 minutes between each batch.
7. The method for preparing a high-transmittance, high-temperature resistant, and high-toughness polyimide material according to claim 5, characterized in that, In S2, the pH value is adjusted using ammonia water with a mass fraction of 25%-28%; the nitrogen flow rate in S2 is in the range of 50-60 mL / min; and the nitrogen flow rate in S3 is 60-80 mL / min.
8. The method for preparing a high-transmittance, high-temperature resistant, and high-toughness polyimide material according to claim 5, characterized in that, The heat treatment is a gradient heating process, and the specific process is as follows: First, raise the temperature to 80-120℃ at a rate greater than 5℃ / min and hold at this temperature for 1-2 hours; Then raise the temperature to 180-250℃ at a rate of 1-5℃ / min and hold at this temperature for 1-2 hours; Finally, raise the temperature to 300-320℃ at a rate of less than 1℃ / min and hold at this temperature for 2-3 hours.
9. The application of a high-transmittance, high-temperature resistant, and high-toughness polyimide material in optoelectronic materials and devices, characterized in that, The polyimide material is the high-transmittance, high-temperature resistant and high-toughness polyimide material according to any one of claims 1-4, or the high-transmittance, high-temperature resistant and high-toughness polyimide material prepared by the preparation method according to any one of claims 5-8.